Integrated transcriptome and metabolome analysis unveil the response mechanism in wild rice (Zizania latifolia griseb.) against sheath rot infection - Chen, Limin; Ma, Yamin; He, Tianjun; Chen, TingTing; Pan, Yiming; Zhou, Dayun; Li, Xiaowei; Lu, Yaobin; Wu, Quancong; Wang, Lailiang (Frontiers in Genetics, 2023)
Sheath rot disease (SRD) is one of the most devastating diseases of Manchurian wild rice (MWR) (Zizania latifolia Griseb). Pilot experiments in our laboratory have shown that a MWR cultivar 'Zhejiao NO.7' exhibits signs of SRD tolerance. To explore Zhejiao No. 7 responses to SRD infection, we used a combined transcriptome and metabolome analysis approach. A total of 136 differentially accumulated metabolites (DAMs, 114 up- and 22 down-accumulated in FA compared to CK) were detected. These up-accumulated metabolites were enriched in tryptophan metabolism, amino acid biosynthesis, flavonoids, and phytohormone signaling. Transcriptome sequencing results showed the differential expression of 11,280 genes (DEGs, 5,933 up-, and 5,347 down-regulated in FA compared to CK). The genes expressed in tryptophan metabolism, amino acid biosynthesis, phytohormone biosynthesis and signaling, and reactive oxygen species homeostasis confirmed the metabolite results. In addition, genes related to the cell wall, carbohydrate metabolism, and plant-pathogen interaction (especially hypersensitive response) showed changes in expression in response to SRD infection. These results provide a basis for understanding the response mechanisms in MWR to FA attack that can be used for breeding SRD-tolerant MWR.